Pharmacological activities of extracts and isolated compounds of Acalypha Fruticosa Forssk. (Euphorbiaceae) - Vinujan, S.; Saravanan, V.; Pholtan, R. (International Journal of Secondary Metabolite, 2022)
Acalypha Fruticosa Forssk is a shrub belonging to the family Euphorbiaceae. A Fruticosa has a wide adaptation through traditional medicinal uses to cure several disorders such as dermatitis, diarrhea, dyspepsia, eye infection, inflammations, and stomachache. This article objects to identify, analyze, and document the reported pharmacological activities of a Fruticosa. Electronic databases namely, PubMed, Sciencedirect, Scopus and Web of Science were employed to identify the related publications from 1900 to August 2021. Compounds such as 1, 2-benzene dicarboxylic acid diisooctylester, and eicosyltrichlorosilane were recognized from different parts of this plant species Until now, only in vivo and in vitro scientific evidence is available for several pharmacological activities for A Fruticosa. Various parts of this plant species have anticancer , antidiabetic, anthelmintic, antibacterial, antileishmanial, and antiplasmodial properties. This work will benefit the investigators on pharmacological and phytochemical investigations of this plant species in the future.
Keywords: Acalypha Fruticosa; Anticancer; Bioactivity; Euphorbiaceae; Traditional Medicine